Language, Culture, and Group Membership: An Investigation Into the Social Effects of Colloquial Australian English. (June 2016) - Kidd, Evan; Kemp, Nenagh; Kashima, Emiko S.; Quinn, Sara
Languages are strong markers of social identity. Multiple features of language and speech, from accent to lexis to grammatical constructions, mark speakers as members of specific cultural groups. In the current article, we present two confederate-scripted studies that investigated the social effects of the Australian hypocoristic use (e.g., uggie, uni, derro )—a lexical category emblematic of Australian culture. Participants took turns with a confederate directing each other through locations on a map. In their directions, the confederate used either hypocoristic (e.g., uni ) or standard forms (e.g., university ). The confederate's cultural group membership and member prototypicality were manipulated by ethnic background and accent: In a highly prototypical in-group condition, the confederate had an Anglo-Celtic background and Australian English (AusE) accent; in a low prototypical in-group condition, the confederate had an Asian background and AusE accent; and in the out-group condition, the confederate had an Asian background and non-AusE accent. Hypocoristic use resulted in significantly higher participant-rated perceived common ground with the confederate when the confederate was an in-group but not an out-group member, which in some instances was moderated by in-group identification. The results suggest that like accents, culturally significant lexical categories function as markers of in-group identity, which influence perceived social closeness during interaction.